Can driver supply disruption alleviate driver shortages? A systems approach. (January 2023) - Chandiran, P.; Ramasubramaniam, M.; Venkatesh, V.G.; Mani, Venkatesh; Shi, Yangyan
Abstract: The driver shortage is a perennial problem in the trucking industry. The review of literature reveals currently there is a lack of holistic approach to address driver shortage problem. This paper presents a systems approach to understand the factors influencing the issue of truck driver shortages in an emerging economy context and their evolution over time. For this study, we define truck driver shortage as: "The shortfall in the market when the quantity of truck drivers supplied is below the number of truck drivers demanded". A system dynamic model has been developed to study a representative truck segment unit. The model is validated and simulated for ten years. The findings from the proposed model indicate that the current system and other environmental factors do not support the truck driver supply increase, drivers and shortages are likely to become acute in the coming years. The study proposes appropriate intervention for the government, and other stakeholders must design proper steps to fill the gap beyond a specific timeframe. The study contributes to the existing literature as a pioneering work on driver shortages in the emerging economy context. Also, the study is one of its kind in using a holistic, quantitative approach to modeling the driver shortage phenomenon. In the process, the study elicits complex relationships that prevail among the factors included in the study. Highlights: A system approach to understanding key issues for truck driver shortages. The current systems and other environmental factors are not associated with the driver supply increase. A pilot study examining driver shortages in the emerging economy context.